A rare case report on the origin of hydatid cyst-how much does it matter in the management? - Chutani, Divya; Kalra, Archit; Tiwari, Rajneesh; Gupta, Poonam; Chaurasia, Ajeet Kumar (Indian Journal of Case Reports, 2025)
Hydatid cysts are most frequently seen in the liver, followed by the lungs, spleen, and pancreas. Here, we present the case of a 17-year-old female who came with complaints of dyspnea, decreased movement on the left lower chest, and absent breath sounds. The blood test showed eosinophilia. The medical literature on hydatid cysts in the gastrohepatic space is altogether lacking. Surgical removal remains the cornerstone of treatment for large or symptomatic hydatid cysts, especially when there is a risk of rupture, compression, or secondary infection. Pre- and post-operative anti-helminthic therapy with albendazole 10 mg/kg/d ×8 weeks reduces recurrence and dissemination. This case underscores the need for a high index of suspicion for hydatid disease of gastro-hepatic space origin in patients from endemic areas presenting with respiratory complaints and its multidisciplinary approach.